2005
DOI: 10.1536/ihj.46.1049
|View full text |Cite
|
Sign up to set email alerts
|

<b>Relationship Between Exercise Intolerance and Levels of Neurohormonal Factors and Proinflammatory Cytokines in Patients With Stable Chronic Heart Failure</b>

Abstract: SUMMARYWe investigated the correlations between exercise intolerance and the plasma levels of neurohormonal factors and proinflammatory cytokines in chronic heart failure (CHF) patients.Sixty-two CHF patients who underwent cardiopulmonary exercise testing (CPX) were enrolled in this study. Peak oxygen uptake (peak VO 2 ) and the plasma concentrations of noradrenaline (NA), brain natriuretic peptide (BNP), and soluble tumor necrosis factor receptors I and II (TNFR-I and -II) were all measured during the CPX. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
2
9
0
1
Order By: Relevance
“…Itoh, et al found a relation between BNP levels and worsening exercise tolerance in patients with stable chronic HF. 12) We found similar results (a negative correlation between exercise duration and BNP levels) in a population of patients with isolated diastolic dysfunction. We also detected a negative correlation between BNP levels and AT and MET values.…”
Section: Discussionsupporting
confidence: 80%
“…Itoh, et al found a relation between BNP levels and worsening exercise tolerance in patients with stable chronic HF. 12) We found similar results (a negative correlation between exercise duration and BNP levels) in a population of patients with isolated diastolic dysfunction. We also detected a negative correlation between BNP levels and AT and MET values.…”
Section: Discussionsupporting
confidence: 80%
“…3,5,6) In patients with chronic HF, the clinical importance of sarcopenia has been recognized in relation to disease severity, reduced exercise capacity, and adverse clinical outcome. [7][8][9][10] Sarcopenia affects approximately 20% of elderly individuals with chronic HF, which exceeds its prevalence in healthy members of the same age group. 11) Nevertheless, the prevalence or impact of sarcopenia on ADHF is still poorly understood.…”
mentioning
confidence: 99%
“…It could not be related to any demographic, morphologic, or surgical variables. This result underscores the fact that even during exercise, there is no excessive wall stress to the atrium or single ventricle causing BNP secretion, as seen in patients after several forms of myocardial dysfunction [21,27,29,34,36].…”
Section: Discussionmentioning
confidence: 59%
“…This holds true for both systolic and diastolic heart failure and is independent of its cause. It also has been shown in many patients with congenital heart defects [5,22,25,35], including those with a univentricular heart and Fontan circulation [23,26].In acquired heart disease, an increase in N-terminus pro-B-type natriuretic peptide (NT-proBNP) during exercise was found related to transient myocardial ischemia [34], the size of a myocardial scar in coronary artery disease [29], and myocardial dysfunction [21,27,36]. However, a more recent report challenged these results because an NTproBNP increase during exercise was related primarily to the level at baseline in a multiple regression analysis [30].…”
mentioning
confidence: 99%
See 1 more Smart Citation